Most Frequent Tumors in Maxillofacial Area Rehabilitated Through Surgical Reconstruction and Prostheses - Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP]; Haddad, Marcela Filie [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Zavanelli, Adriana Cristina [UNESP] (Lippincott Williams & Wilkins, 2010)
Cancer is regarded as the abnormal cellular multiplication; it is not controlled by the organism; and its cells present a differentiated DNA. Initially, the disease does not show clinical signs, but it can be diagnosed by laboratorial examinations. When tumors are present in the maxillofacial area, they can entail the loss of these area organs, which become responsible for the carrier's social environment exclusion. This paper aimed at showing, through a literature review, the cancers that more commonly happen in the face and the possibilities of regenerating in the patient mutilated through surgical reconstruction and prostheses.
Keywords: Maxillectomy and midfacial defects; free tissue transfer; maxillofacial prostheses; surgery reconstruction